Evaluasi sebagai Pilar dalam Meningkatkan Mutu Pembelajaran PAI di SMP Negeri 4 Padang Panjang - Dari, Yuni Wulan; Remiswal, Remiswal; Khadijah, Khadijah (YASIN, 2025)
This study is motivated by the importance of evaluation as a key pillar in improving the quality of Islamic Education (Pendidikan Agama Islam, PAI) learning at SMP Negeri 4 Padang Panjang. However, the implementation of evaluation still faces several challenges, such as students’ low awareness in practicing Islamic values they have learned and the limited parental supervision of their children's religious practices outside the home. The aim of this study is to examine the extent to which evaluation contributes to enhancing the quality of PAI learning. A qualitative approach was used, with data collected through observation, interviews, and documentation. The findings indicate that evaluation plays a central role in determining the success of the PAI learning process. Educational success is reflected in the structured implementation of evaluation by teachers through planning and execution stages. All educators at SMP Negeri 4 Padang Panjang are actively involved in conducting evaluations as a collective effort to improve learning quality. Supporting factors include teacher commitment and school-wide coordination, while inhibiting factors include time constraints and limited external supervision. Nevertheless, teachers continue to strive to overcome these obstacles to ensure that evaluations are carried out optimally and the goal of improving the quality of Islamic education is achieved. The implications of this study affirm that the success of learning quality heavily depends on systematic and continuous evaluation practices.